1985
DOI: 10.1016/0014-5793(85)80170-8
|View full text |Cite
|
Sign up to set email alerts
|

An unusual linkage between polysaccharides and some major proteins from the outer membrane of Escherichia coli

Abstract: A small population of OmpA, a major protein from the outer membrane of Escherichia coli, was found covalently associated with either lipopolysaccharide or O-antigen polysaccharide. Radioactive oligosaccharide was elicited linked to OmpA after treatment of the membranes with periodate that hydrolyzed large sugars. Association of saccharides to OmpA could be enhanced by treatment of the outer membrane with NaBH,.(E. coli)Outer membrane

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that bacterial LPS can bind to or associate with many proteins including serum LPSbinding protein LBP [12], CD14 [13], the macrophage scavenger receptor, the beta2 integrins [14], hemoglobin [15], moth hemolin (an insect member of the Ig-superfamily) [16], OmpA of Escherichia coli [17], the S2 subunit of pertussis toxin [18], the 39 kDa membrane protein of Hae- …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that bacterial LPS can bind to or associate with many proteins including serum LPSbinding protein LBP [12], CD14 [13], the macrophage scavenger receptor, the beta2 integrins [14], hemoglobin [15], moth hemolin (an insect member of the Ig-superfamily) [16], OmpA of Escherichia coli [17], the S2 subunit of pertussis toxin [18], the 39 kDa membrane protein of Hae- …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that bacterial LPS can bind to or associate with many proteins including serum LPSbinding protein LBP [12], CD14 [13], the macrophage scavenger receptor, the beta2 integrins [14], hemoglobin [15], moth hemolin (an insect member of the Ig-superfamily) [16], OmpA of Escherichia coli [17], the S2 subunit of pertussis toxin [18], the 39 kDa membrane protein of Haemophilus infl uenzae type b [19], and several plasma proteins of rainbow trout [20]. More pertinent to the present study, however, were LPS-protein was loaded fi rst into lanes 1-8 and then the following amounts of heat-inactivated gp70 in 1 × SPB were loaded on top of the LPS: lane (1) 0 μg, (2) 0.02 μg, (3) 0.04 μg, (4) 0.06 μg, (5) 0.08 μg, (6) 0.1 μg, (7) 0.12 μg, (8) 0.2 μg, and (9) 0.1 μg.…”
Section: Resultsmentioning
confidence: 99%